Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) as independent predictors of outcome in infective endocarditis (IE) - Marwa Sayed Meshaal; Abdo Nagi; Ahmed Eldamaty; Wae’el Elnaggar; Mervat Gaber; Hussien Rizk (The Egyptian Heart Journal, 2019)
Abstract Background Early and accurate risk assessment is an important clinical demand in patients with infective endocarditis (IE). The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are independent predictors of prognosis in many infectious and cardiovascular diseases. Very limited studies have been conducted to evaluate the prognostic role of these markers in IE. Results We analyzed clinical, laboratory, and echocardiographic data and outcomes throughout the whole period of hospitalization for a total of 142 consecutive patients with definitive IE. The overall in-hospital mortality was 21%. Major complications defined as central nervous system embolization, fulminant sepsis, acute heart failure, acute renal failure, and major artery embolization occurred in 38 (27%), 34 (24%), 32 (22.5%), 40 (28%), and 90 (63.4%) patients, respectively. The NLR, total leucocyte count (TLC), neutrophil percentage, creatinine, and C-reactive protein (CRP) level obtained upon admission were significantly higher in the mortality group [p ≤ 0.001, p = 0.008, p = 0.001, p = 0.004, and p = 0.036, respectively]. A higher NLR was significantly associated with fulminant sepsis and major arterial embolization [p = 0.001 and p = 0.028, respectively]. The receiver operating characteristic (ROC) curve of the NLR for predicting in-hospital mortality showed that an NLR > 8.085 had a 60% sensitivity and an 84.8% specificity for an association with in-hospital mortality [area under the curve = 0.729, 95% confidence interval (CI) 0.616–0.841; p = 0.001]. The ROC curve of the NLR for predicting severe sepsis showed that an NLR > 5.035 had a 71.8% sensitivity and a 68.5% specificity for predicting severe sepsis [area under the curve 0.685, 95% CI 0.582–0.733; p = 0.001]. The PLR showed no significant association with in-hospital mortality or in-hospital complications. Conclusion A higher NLR, TLC, neutrophil percentage, creatinine level, and CRP level upon admission were associated with increased in-hospital mortality and morbidity in IE patients. Furthermore, a lower lymphocyte count/percentage and platelet count were strong indicators of in-hospital mortality among IE patients. Calculation of the NLR directly from a CBC upon admission may assist in early risk stratification of patients with IE.